2015
DOI: 10.1063/1.4907208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of annealing temperature on the mechanical and electrical properties of sputtered aluminum nitride thin films

Abstract: Aluminium nitride (AlN) is a promising material for challenging sensor applications such as process monitoring in harsh environments (e.g., turbine exhaust), due to its piezoelectric properties, its high temperature stability and good thermal match to silicon. Basically, the operational temperature of piezoelectric materials is limited by the increase of the leakage current as well as by enhanced diffusion effects in the material at elevated temperatures. This work focuses on the characterization of aluminum n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…[201][202][203][204] Interestingly, recent investigations of the electrical properties of sputter deposited and PEALD AlN have also reported electrical leakage to occur predominantly by the PF mechanism. [205][206][207] More recent electrically detected magnetic resonance (EDMR) measurements by Mutch et al have conclusively shown that electron transport in PECVD SiN:H specifically occurs through silicon dangling bond defect states located in the mid-upper portion of the SiN bandgap. 208,209 Owing to the similar IV characteristics, deduced leakage mechanism, and band structure, 210 it seems plausible that electron transport in amorphous AlN (independent of deposition method) may also occur through Al dangling bond defect states.…”
mentioning
confidence: 99%
“…[201][202][203][204] Interestingly, recent investigations of the electrical properties of sputter deposited and PEALD AlN have also reported electrical leakage to occur predominantly by the PF mechanism. [205][206][207] More recent electrically detected magnetic resonance (EDMR) measurements by Mutch et al have conclusively shown that electron transport in PECVD SiN:H specifically occurs through silicon dangling bond defect states located in the mid-upper portion of the SiN bandgap. 208,209 Owing to the similar IV characteristics, deduced leakage mechanism, and band structure, 210 it seems plausible that electron transport in amorphous AlN (independent of deposition method) may also occur through Al dangling bond defect states.…”
mentioning
confidence: 99%
“…This is evidence that annealing releases the stress in the film and decreases the stress effect on the crystal lattice [14]. AlN annealed at 700°C showed improved electrical properties, whereby the flatband voltages (VFB) value was positive and the peak intensity increased [15]. Post-deposition rapid thermal annealing between 900°C and 1300°C showed a reduction of defects in the AlN thin films' crystallization process and was identified by the increase of grain size of the original crystallites as well as the growth of new small grains exhibiting tensile strain [16].…”
Section: Introductionmentioning
confidence: 90%
“…The distance between target and substrate is fixed at 65 mm. The parameters were chosen based on pre-investigations for good caxis orientation [7,11]. The total film thickness h is 2 µm.…”
Section: Methodsmentioning
confidence: 99%
“…AlN promises operation up to 700°C even in pure oxygen atmosphere for two hours without measureable film degeneration [7]. Whereas, AlScN has a higher d33 and therefore the electromechanical coupling factor is increased by a factor of ~3, compared to pure AlN [8][9][10].…”
Section: Introductionmentioning
confidence: 99%